Case Report: Diagnosis of Primary Klebsiella pneumoniae in Cervical Spine by Metagenomic Next-Generation Sequencing - Li, Tao; Gao, Qile; Guo, Chaofeng; Li, Yanbing (Frontiers in Surgery, 2022)
Introduction:Spinal infection is a disease that affects the intervertebral discs or adjacent paravertebral tissue in the vertebral body. There are few reports of spinal infections caused by Klebsiella pneumoniae(K.pneumoniae). Cervical spine infection by K.pneumoniae especially preoperative is extremely rare. Nowadays, metagenomic next-generation sequencing(mNGS) has led to the accurate and timely diagnoses of numerous infectious diseases. Case presentation: We describe a case of a 64-year-old woman, with a chief complaint of the neck, shoulder, and upper limb pain for 10 days. The patient had symptoms of abscess compression before surgery, and inflammatory indicators such as Erythrocyte sedimentation rate(ESR), C-reactive protein(CRP) and procalcitonin(PCT) were significantly elevated. The patient's imaging suggested cervical infectious lesions, and the patient had no symptoms of tuberculosis poisoning, and tubercul-related blood drawing indexes were negative. The patient was diagnosed as cervical suppurative infection before surgery. For the patient who failed conservative treatment and had abscess compression or other surgical indications, we performed anterior cervical surgery to remove the lesion at an early stage, and collected intraoperative specimens for culture and mNGS. Postoperative antibiotic treatment was adjusted according to the etiology and drug sensitivity. Conclusion: This case suggests that the clinical symptoms of K.pneumoniae infection are not typical and the imaging examination lacks specificity. When the clinical diagnosis of etiology is not clear or there are symptoms such as abscess compression, early surgical specimens can be collected for culture and mNGS to identify the pathogen, and postoperative sensitive antibiotics can be used to continue treatment. This helps to identify the cause as early as possible, treat it effectively early, relieve symptoms, prevent complications and keep the spine stable.